New species and new records of fruit flies of tribe Acanthonevrini (Diptera: Tephritidae: Phytalmiinae) from India - David, K. J.; Hancock, D. L.; Salini, S.; Ningthoujam, Kennedy; Khemrajji, Hatwar Nikhil; Abhishek, V.; Gracy, R. G.; Sushil, S. N. (Zootaxa, 2024)
Two new species of Phytalmiinae belonging to the tribe Acanthonevrini are described from India, namely Ptilona confracta David & Hancock, sp. nov. from Arunachal Pradesh and Tritaeniopteron obscurum David, Salini & Nikhil, sp. nov. from Karnataka. Tritaeniopteron de Meijere is recorded for the first time from India based on the new species T. obscurum; male and female syntypes of T. punctatipleurum (Senior-White) are dissected and illustrated. A female of Erectovena desperata (Hering), both sexes of Felderimyia gombakensis Hancock & Drew and Phorelliosoma hilaratum Hering, recorded for the first time from India are dissected and illustrated. An illustrated key to 23 species of Acanthonevrini belonging to 12 genera from India is included. DNA barcode sequences of Felderimyia fuscipennis Hendel, Ptilona confracta, P. confinis (Walker), Rioxoptilona dunlopi (van der Wulp) and Themara yunnana Zia were obtained and reported.